A great way to bring up health behaviour topics at playgroup: a qualitative evaluation of the Healthy Conversations @ Playgroup program - Georgia Middleton; Brittany J. Johnson; Dimity Dutch; Stewart G. Trost; Rebecca Byrne; Hayley E. Christian; Anna Henry; Caroline O. Terranova; Kate E. Williams; Li Kheng Chai; Denise S. K. Brookes; Kate Simon; et al. (BMC, 2024)
Abstract Background The early years is a critical stage to establish optimal nutrition and movement behaviours. Community playgroups are a relaxed environment for parents with a focus on social connection and supporting parents in their role as 'First Teachers'. Playgroups are therefore an opportunistic setting to promote health behaviours in the early years. To support parents with young children around healthy lifestyle behaviours, the Healthy Conversations @ Playgroup program was delivered in urban and regional areas, across three Australian jurisdictions between 2021-2023. Objective This qualitative evaluation aimed to understand how the Healthy Conversations @ Playgroup program was experienced by parents, playgroup coordinators and peer facilitators. Design Semi-structured virtual interviews and focus groups were conducted with parents, playgroup coordinators (i.e., person responsible for coordinating the playgroup) and peer facilitators (i.e., trained facilitator for the program) that participated in the Healthy Conversations @ Playgroup study. Transcripts were analysed following a thematic analysis approach. Results Twenty-eight playgroup parents, coordinators or peer facilitators participated in one of 8 focus groups or 5 interviews. Four themes were developed: Program strengths and challenges; Setting strengths and challenges; Factors that impact program delivery; Participant's suggestions for future program delivery. Conclusions The Healthy Conversations @ Playgroup program was valued by parents, providing validation and normalisation of parenting practices, and fostering a shared experience of parenting. Playgroups are a convenient setting for families to attend. The dynamic and distracting nature of the playgroup setting were carefully considered when designing the program. Strategies to further enhance program engagement could include use of coordinator or parent champions, tailored delivery, and extending the reach to other family members. Trial registration Australian New Zealand Clinical Trials Registry ACTRN12621000055808, registered 22 January 2021, https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=380890